Examining sufficiency and equity in the geographic distribution of physicians in Japan: a longitudinal study - Yuichi Imanaka; Susumu Kunisawa; Koji Hara; Tetsuya Otsubo (BMJ Open)
Objectives The objective of this study was to longitudinally examine the geographic distribution of physicians in Japan with adjustment for healthcare demand according to changes in population age structure.Methods We examined trends in the number of physicians per 100 000 population in Japan's secondary medical areas (SMAs) from 2000 to 2014. Healthcare demand was adjusted using health expenditure per capita. Trends in the Gini coefficient and the number of SMAs with a low physician supply were analysed. A subgroup analysis was also conducted where SMAs were divided into 4 groups according to urban–rural classification and initial physician supply.Results The time-based changes in the Gini coefficient and the number of SMAs with a low physician supply indicated that the equity in physician distribution had worsened throughout the study period. The number of physicians per 100 000 population had seemingly increased in all groups, with increases of 22.9% and 34.5% in urban groups with higher and lower initial physician supply, respectively. However, after adjusting healthcare demand, physician supply decreased by 1.3% in the former group and increased by 3.5% in the latter group. Decreases were also observed in the rural groups, where the number of physicians decreased by 4.4% in the group with a higher initial physician supply and 7.6% in the group with a lower initial physician supply.Conclusions Although the total number of physicians increased in Japan, demand-adjusted physician supply decreased in recent years in all areas except for urban areas with a lower initial physician supply. In addition, the equity of physician distribution had consistently deteriorated since 2000. The results indicate that failing to adjust healthcare demand will produce misleading results, and that there is a need for major reform of Japan's healthcare system to improve physician distribution.